Exploring the intersection of natural sciences and information technology via entropy and randomness - Anne M. Luescher; Reinhard Heckel; Robert N. Grass (Nature Communications)
Abstract Physical sources of randomness are indispensable for information technology and cryptography. Yet, the usefulness of random processes seems to be ignored by many natural science researchers, who are exposed to the downsides of randomness, which adds noise and uncertainty to experiments. Here, we look at experimental science through the lens of information theory, with entropy as a key concept that bridges multiple fields. By examining physical unclonable functions and molecular information technology, we highlight interdisciplinary research leveraging these synergies. With this perspective, we hope to inspire the fascination of randomness and entropy in science, encouraging new research directions across different disciplines.